Comparison of Knowledge and Information-Seeking Behavior Between Medical and Non- Medical Students at Universitas Muhammadiyah Sumatera Utara Regarding COVID-19 Vaccination - Fahreza, Muhammad; Yulistika, Ratih (Universitas Muhammadiyah Sumatera Utara, 2026)
Abstract: Coronavirus is part of a family of viruses that cause illnesses ranging from the common cold to more severe diseases such as Middle East Respiratory Syndrome (MERS-CoV) and severe acute respiratory syndrome (SARS-CoV). Since then, various countermeasures have been carried out, one of which is the COVID-19 vaccination program aimed at accelerating the formation of herd immunity. This study was conducted using a cross-sectional approach with a non-probability consecutive sampling method. Data collection was carried out using primary data obtained directly from respondents through questionnaires. The sample in this study consisted of 100 respondents, divided into 50 medical students and 50 non-medical students. The results showed that among medical students, 42% had good knowledge and 12% had poor knowledge, while among non-medical students, only 6% had good knowledge and 42% had poor knowledge. These results may be influenced by factors such as educational background, access to information sources, and learning environment.